2018
DOI: 10.1063/1.5004605
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic metamaterial panel for both fluid passage and broadband soundproofing in the audible frequency range

Abstract: We present the design, including an experimental demonstration, of an acoustic metamaterial panel aimed at reducing incoming broadband noise in the audible frequency range while allowing an incoming fluid to pass through the holes formed in the panel. The noise reduction performance of the proposed acoustic metamaterial panel is attributed to an array of annular cavities enclosing the fluid passage holes. The acoustic behavior of the acoustic metamaterial panel is theoretically analyzed by the transfer matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…A maximum transmission loss of 40 dB is achieved through the structure signifying its potential for future applications. Jung et al [82] presented a muffler type acoustic metamaterial panel for ventilated sound attenuation. As shown in Figure 6c, each unit cell of the metapanel consisted of one circular duct enclosed by an array of annular cavities.…”
Section: Acoustic Metamaterials As Soundproof Ventilated Windowsmentioning
confidence: 99%
“…A maximum transmission loss of 40 dB is achieved through the structure signifying its potential for future applications. Jung et al [82] presented a muffler type acoustic metamaterial panel for ventilated sound attenuation. As shown in Figure 6c, each unit cell of the metapanel consisted of one circular duct enclosed by an array of annular cavities.…”
Section: Acoustic Metamaterials As Soundproof Ventilated Windowsmentioning
confidence: 99%
“…2(a), as the frequency increases initially, the sound pressure level values decrease rapidly, have a minimum value at a specific frequency (4529.1 Hz in the case of N=5), and then rise again. In other words, it has a resonant property, which can be treated as the result of the interaction between the particle vibration in the direction of sound propagation in the circular duct and the particle vibration perpendicular to the direction of sound propagation in the annular cavity [14]. This property appears regardless of the number of annular cavities.…”
Section: B Calculation Results Of Sound Pressure Level In Case Of No ...mentioning
confidence: 99%
“…A finite element based theoretical and numerical approach was used to evaluate the sound characteristics in the frequency range of 125 Hz to 2000 Hz. Jung et al [93] demonstrated an acoustic metamaterial panel for both fluid passage and broadband soundproofing in the audible frequency range of 2000 Hz to 4000 Hz. The unit cell of the panel consisted of a circular through duct enclosed with multiple annular circumferential cavities.…”
Section: Helmholtz Resonatorsmentioning
confidence: 99%